Contrast‐enhanced magnetic resonance angiography of the peripheral arteries: Technique, tips, pitfalls and problems. Issue 2 (2nd April 2013) - Welman, Christopher J; Harrison, Colin; Low, Ronny S
Summary Contrast‐enhanced magnetic resonance angiography is a reliable way to assess peripheral vascular disease. This article reviews the basic physics behind this technique and discusses our institution's experience with regard to the clinical role, recent advances in image acquisition and use of contrast agents. Problems that can affect image quality and interpretation are also highlighted.